The EccDNA Replicon: A Heritable, Extranuclear Vehicle That Enables Gene Amplification and Glyphosate Resistance in Amaranthus palmeri. Issue 7 (23rd April 2020) - Molin, William T.; Yaguchi, Allison; Blenner, Mark; Saski, Christopher A.
Abstract : The eccDNA replicon is a large extranuclear circular DNA that is composed of a sophisticated repetitive structure and harbors the EPSPS and several other genes that are transcribed during glyphosate stress. Abstract: Gene copy number variation is a predominant mechanism used by organisms to respond to selective pressures from the environment. This often results in unbalanced structural variations that perpetuate as adaptations to sustain life. However, the underlying mechanisms that give rise to gene proliferation are poorly understood. Here, we show a unique result of genomic plasticity in Amaranthus palmeri : a massive, 400-kb extrachromosomal circular DNA (eccDNA) that harbors the 5-ENOYLPYRUVYLSHIKIMATE-3-PHOSPHATE SYNTHASE ( EPSPS ) gene and 58 other genes whose encoded functions traverse detoxification, replication, recombination, transposition, tethering, and transport. Gene expression analysis under glyphosate stress showed transcription of 41 of these 59 genes, with high expression of EPSPS, as well as genes coding for aminotransferases, zinc finger proteins, and several uncharacterized proteins. The genomic architecture of the eccDNA replicon is composed of a complex arrangement of repeat sequences and mobile genetic elements interspersed among arrays of clustered palindromes that may be crucial for stability, DNA duplication and tethering, and/or a means of nuclear integration of the adjacent and intervening sequences. Comparative analysis of orthologous genes in grain amaranth ( Amaranthus hypochondriacus ) and waterhemp ( Amaranthus tuberculatus ) suggests that higher order chromatin interactions contribute to the genomic origins of the A. palmeri eccDNA replicon structure.